Barriers and enablers that influence guideline-based care of geriatric fall patients presenting to the emergency department. Issue 12 (24th September 2019) - Parks, Adam; Eagles, Debra; Ge, Yipeng; Stiell, Ian G; Cheung, Warren J
Abstract : Background: Geriatric patients commonly present to the ED after a fall. Recent evidence suggests that ED physicians are poorly adherent to published ED-specific geriatric fall guidelines. This study applied a theoretical domains framework (TDF) approach to systematically investigate barriers and enablers in the provision of guideline-based care to ED geriatric fall patients. Methods: From June to September 2017, semistructured interviews of staff ED physicians practising in Ontario, Canada, were conducted and analysed. An interview guide based on the TDF was used to capture 14 domains influencing provision of guideline-based care. Relevant domains were identified based on frequencies of beliefs, existence of conflicting beliefs and evidence of strong beliefs that would influence provision of guideline-based care. Results: Eleven interviews were conducted with practising ED physicians. Thirty belief statements were identified across 13 relevant TDF domains (all except Optimism ). Prominent themes included lack of knowledge, paucity of evidence, heterogeneous self-perceived skills, perceived increased time and workload, importance of allied health support, inconsistently available allied health workers, lack of positive reinforcement, emotions negatively impacting these clinical encounters and support for memory aids. Overall, ED physicians were supportive of guideline implementation, and believe it will lead to better outcomes for geriatric fall patients. Conclusion: This study identified important barriers and enablers to provision of guideline-based care in geriatric ED fall patients. Based on these findings, future implementation of guidelines nationally and internationally should focus on improving knowledge and training on guidelines, improving positive reinforcement for guideline-appropriate management, greater allied health support and further research to support guidelines.